SCHOOL-PARENT COMMUNICATION PRACTICES FROM AN ISLAMIC PERSPECTIVE AND THEIR IMPACT ON STUDENT LEARNING OUTCOMES - Muhibbudin Irsyad; Devi Sulaeman; Mia Audina Musyadad; Agus; Asep Supriatna Asep (Indonesian Journal of Elementary Education (IJETE), 2026)
Education is an ecosystem involving various elements, with the family as its primary foundation. Schools then act as strategic partners, continuing, strengthening, and developing the educational process in a systematic and structured manner. Effective and valuable communication is believed to be able to build sustainable educational synergy. This study aims to analyze school-parent communication practices from an Islamic perspective and their impact on student learning outcomes at Nurul Hidayah Elementary School in Kutawaluya District. The study used a qualitative approach with a case study. Data were collected through observation, in-depth interviews, and documentation studies, then analyzed interactively through the stages of reduction, presentation, and drawing conclusions. The results indicate that communication practices occur formally and informally, are integrated with the values of trust and deliberation, and encourage active parental involvement in home learning support. Dialogic and persuasive communication contributes to improved student discipline, learning readiness, and responsibility. Integrating Islamic values into communication practices strengthens collaborative relationships between schools and families. The implications of this research emphasize the importance of developing an Islamic values-based educational communication model as a strategy to strengthen school-parent partnerships in improving student learning outcomes.